A justiça restaurativa no enfrentamento à violência de gênero: avaliação de política pública sobre novas alternativas de acesso à justiça na cidade de Iguatu Ceará - Silva, Antonio Vinícius Lourenço da (2024)
The present research project aims to analyze the relationship between restorative justice and its role in addressing violence against women, examining the limitations of the retributive justice model in Brazilian law, with a focus on access for women victims of domestic violence. Similarly, the work addresses the impacts of restorative justice in Brazil and how this phenomenon behaves concerning issues of violence. Here, the object of study is the evaluation of public policy regarding the phenomenon of domestic violence against women and its connection with restorative actions, based on Resolution 225/2016 of the National Council of Justice. As a research problem, it seeks to answer whether restorative practices based on the aforementioned Resolution act efficiently in dealing with the scenario of violence against women. Adhering to the investigation's objective, it aims to understand, through the application of restorative justice, the possibility of reducing violence rates against women in the state of Ceará. For this purpose, quantitative and qualitative methodologies were instrumentalized, using as sources the online sites of judicial bodies, as well as conducting interviews with legal professionals, public security officials, and activists from groups fighting against gender violence operating in the municipality of Iguatu/Ceará. The temporal scope of the research covered the years 2016 to 2023. In the final part of this dissertation, the evaluation of the public policy of Resolution 225/2016 was conducted, followed by the consequent conclusion.